2007
DOI: 10.1093/ecam/nem040
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Pulmonary Diseases and Respiratory‐Related Conditions with Inhaled (Nebulized or Aerosolized) Glutathione

Abstract: Reduced glutathione or simply glutathione (γ-glutamylcysteinylglycine; GSH) is found in the cytosol of most cells of the body. GSH in the epithelial lining fluid (ELF) of the lower respiratory tract is thought to be the first line of defense against oxidative stress. Inhalation (nebulized or aerosolized) is the only known method that increases GSH's levels in the ELF. A review of the literature was conducted to examine the clinical effectiveness of inhaled GSH as a treatment for various pulmonary diseases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 37 publications
1
33
0
1
Order By: Relevance
“…4 Furthermore, reduced glutathione concentration and/or a disproportionate ratio of GSH:GSSG has been associated with a number of diseases, including cancer, human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS), hepatitis, type 2 diabetes, Parkinson's disease, and cystic fibrosis. 2,[8][9][10][11][12][13][14] Although no experimental research to date has demonstrated disease prevention from GSH supplementation or other strategies to specifically increase GSH, observational research suggests increased dietary glutathione intake has been associated with reduced risk for oral cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Furthermore, reduced glutathione concentration and/or a disproportionate ratio of GSH:GSSG has been associated with a number of diseases, including cancer, human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS), hepatitis, type 2 diabetes, Parkinson's disease, and cystic fibrosis. 2,[8][9][10][11][12][13][14] Although no experimental research to date has demonstrated disease prevention from GSH supplementation or other strategies to specifically increase GSH, observational research suggests increased dietary glutathione intake has been associated with reduced risk for oral cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, to lesser degrees, intravenous, intramuscular, intrabronchial (i.e., nebulized), and intranasal glutathione administrations have all been used to increase circulating or tissue-specific GSH levels. 12,13,21 Minimal experimental evidence has demonstrated significant increases in blood or intracellular levels of GSH through oral supplementation with reduced GSH. Animal in vivo data suggest that oral GSH is absorbed in rats.…”
Section: Introductionmentioning
confidence: 99%
“…The protective role of GSH in regard to the lower respiratory tract has been suggested; hence, use of GSH inhalations might be beneficial for cystic fibrosis treatment (Prousky, 2008;Day, 2005). In our study, the relatively small sample size of the patientcohort was a limitation.…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence from the literature indicating that oxidized and reduced GSH can serve as important cell signaling factors (39,69,103). However, the role of S-glutathionylation in ion transport remains unclear, despite widespread clinical treatment of respiratory-related conditions (in oxidatively stressed lung) with inhaled GSH (78).…”
Section: Overview Of Ion Channels and Transporters In Lung Epitheliamentioning
confidence: 99%